THE QUR'ANIC PERSPECTIVE IN THE CREATION OF DANCE AS AN ARTISTIC EXPRESSION: THE QUR'ANIC PERSPECTIVE IN THE CREATION OF DANCE AS AN ARTISTIC EXPRESSION - Nursyam, Romi (International Journal of Performing Arts (IJPA), 2025)
This article examines the creation of dance works through the perspective of the Quran.The research was conducted in Jakarta. The author will focus on the religious normsthat bind local and Islamic communities, which will serve as a foundation for discussingthe creation of artwork. The research method used is descriptive qualitative, with datacollection conducted through interviews, observations, and literature review.This discussion is considered urgent and crucial because Indonesia, with a Muslimmajority, must utilize their religious law as a source in creating artwork, especially forthose of the Islamic faith. This ensures that the resulting artwork can also providespiritual knowledge and enlightenment. This ensures that the resulting dance artworkis relevant to Islamic values and norms.